The Relationship Between Heavy Metals Pb, Cr, and Hg in the Water and Sediments of the Ciliwung River with the Content of Pb, Cr, and Hg in Plankton - Khoe Susanto Kusumahadi (Universitas Nasional Jakarta, 2023)
This research aims to investigate the relationship between heavy metals Pb, Cr, and Hg in water and sediments with the concentrations of Pb, Cr, and Hg in the water, sediments, and plankton of the Ciliwung River. Heavy metals Pb, Cr, and Hg concentrations in water, sediments, and plankton generally appear to fluctuate. As we move downstream, the concentrations of these heavy metals tend to increase in line with increased human activities in the downstream area, such as industrial, service, trade, and residential activities. There are significant differences in the concentrations of Pb, Cr, and Hg in plankton based on observation locations (p<0.05), whereas based on repetitions (seasons), only Pb and Hg exhibit significant differences (p<0.05). Correlation tests indicate that the relationship between the concentration of Hg in water and the concentration of Hg in plankton is not statistically significant (p>0.05). Similarly, the relationships between Pb, Cr, and Hg concentrations in sediments and Pb, Cr, and Hg in plankton are not statistically significant (p>0.05).